Soviet-German Legal Cooperation in the Investigation of Nazi Crimes - Tytarenko, Dmytro (Narzędzia wojny, 2023)
The article explores the peculiarities of the investigation of the Nazi crimes, which were committed in the Soviet Union during the occupation. This article focuses on the cooperation between the German and Soviet justice systems, which aimed to provide the German side with additional information concerning the circumstances and perpetrators of the crimes. The acts of the "Extraordinary State Commission for Ascertaining and Investigating Crimes Perpetrated by the German-Fascist Invaders and their Accomplices», the protocols of interrogation of Nazi criminals, their accomplices and witnesses were the most important of them. The using of materials received from the Soviet side, the identification of Nazi criminals were connected with such problems: incomplete spelling of the names of the suspected persons, incorrectly indicated military ranks or positions, the lack of information about suspected persons with respect to particular crimes. Despite some political stereotypes, created by the Cold War, it was some relatively successful examples of cooperation between the two legal systems in the area of bringing Nazi criminals to justice.